Influence of washing on the adhesion between 3D-printed TPU and woven fabrics - Jannik Störmer (TU Dresden; Faculty of Mechanical Science and Engineering;Chair of Development and Assembly of Textile Products, 2021)
3D printing on textile fabrics can be used to create composites with position-dependent mechanical, water-resistant, magnetic or other properties. An important prerequisite to use such composites technologically or for design purposes is a sufficient adhesion between both materials. While previous studies revealed that soft, elastic printing polymers were advantageous to prepare connections with a high adhesion, not much research has been performed yet on the dependence of the adhesion on textile fabric structure, heat post-treatment, and the influence of washing, which is necessary for most applications of such composites. Here we investigate composites from thermoplastic polyurethane (TPU) 3D-printed on two different woven cotton fabrics. Besides the expected strong correlation of the adhesion with the distance between nozzle and printing bed, we find a higher adhesion on the thinner fabric and an increase in the adhesion after one washing cycle.